Study on casting process of array holes. Issue 9 (October 2016) - Jin, M.; Qu, Y.; Qing, G.; Chen, R.; Li, G.; You, J.; Li, R.
Abstract Aluminum array holes were prepared by casting method which was carried out by using stainless steel wires coated with graphite coating as hole core. It has been verified by analyzing that because of the molten metal filling, ability was mainly affected by metallostatic pressure, surface tension, and melt viscosity. In this experiment, the array hole with a regular arrangement, round shape, and uniform diameter can be acquired under the condition that center spacing of adjacent hole core be greater than the diameter of the hole core. And the average diameter of array holes was about 0.55 mm and center spacing of adjacent hole was about 2.95 mm, there were almost no defects on the specimen.